Industry Collaborations of Research Teams: Are They Penalized or Rewarded in the Grant Evaluation Process? - Öcalan-Özel, Sıla; Llerena, Patrick (Frontiers in Research Metrics and Analytics, 2021)
This paper explores the relationship between the industry collaborations of grant applicant teams and the outcomes of a multi-stage grant evaluation process. We study this relationship by focusing on two possible channels of impact of industry engagement – team diversity (or the diversity effect) and prior collaboration experience (or the experience effect) – and examine their influence on the evaluators’ decision by using the proxies of direct industry engagement (i.e. the involvement of a company-affiliated researcher in the grant applicant team) and indirect industry engagement (i.e. joint publications with a company-affiliated researcher prior to the grant application), respectively. We analyze data extracted from the application and review materials of a multi-disciplinary, pan-European research funding scheme – European Collaborative Research (EUROCORES) – for the period 2002–2010, and conduct an empirical investigation of its three consecutive grant evaluation stages at the team level. We find that teams presenting an indirect engagement are more likely to pass the first stage of selection whereas no significant relationships are found at any of the three evaluation stages for teams presenting a direct engagement. Our findings point to the heterogeneity of the decision-making process within a multi-stage grant evaluation scheme and suggest that the policy objective of fostering university–industry collaboration does not significantly impact the funding process.